2009
DOI: 10.1152/ajpregu.90651.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GLUT4 expression in denervated skeletal muscle

Abstract: Denervation by sciatic nerve resection causes decreased muscle glucose transporter 4 (GLUT4) expression, but little is known about the signaling events that cause this decrease. Experiments were designed to test the hypothesis that decreased GLUT4 expression in denervated muscle occurs because of decreased calcium/CaMK activity, which would then lead to decreased activation of the transcription factors myocyte enhancer factor 2 (MEF2) and GLUT4 enhancer factor (GEF), which are required for normal GLUT4 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…3d). Given that the human Glut4 promoter was well characterized and regulated by many proteins such as class II histone deacetylases, ZAC1, and MEF2A, [24][25][26][27][28][29] to obtain further insight into the potential function of PPARα and GATA-6, we performed transient transfection assays on the 2441-bp human Glut4 promoter; as shown in Fig. 3e, PPARα and GATA-6 still displayed synergistic activation, which further demonstrated the functional cooperation between PPARα and GATA-6.…”
Section: Gata-6 Enhances Pparα-induced Glut4 Activationmentioning
confidence: 89%
“…3d). Given that the human Glut4 promoter was well characterized and regulated by many proteins such as class II histone deacetylases, ZAC1, and MEF2A, [24][25][26][27][28][29] to obtain further insight into the potential function of PPARα and GATA-6, we performed transient transfection assays on the 2441-bp human Glut4 promoter; as shown in Fig. 3e, PPARα and GATA-6 still displayed synergistic activation, which further demonstrated the functional cooperation between PPARα and GATA-6.…”
Section: Gata-6 Enhances Pparα-induced Glut4 Activationmentioning
confidence: 89%
“…Genetic ablation of CaMKIV in monocyte-derived dendritic cells leads to a marked defect in typical markers of mature myeloid DC in response to LPS, involving MHC-II molecule I-A and TLR4 [15] . Skeletal muscle cells have been proposed to be the facultative APCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies previously implicate CaMKIV in the Ca 2+ -dependent regulation of muscle gene expression, specifically in the activation of mitochondrial biogenesis and oxidative enzyme expression [1, 15-17]. However, other studies show a lack of CaMKIV expression in skeletal muscle, and CaMKIV is indicated not required for the maintenance of slow-twitch muscle phenotype and endurance training-induced mitochondrial biogenesis in murine skeletal muscle [18].…”
Section: Introductionmentioning
confidence: 99%
“…This increase in GLUT-4 in myotubes probably results from enhanced expression of MEF2A and MEF2D, which were shown to form heterodimer and activate GLUT-4 gene transcription in striated muscle 27) . In addition, transgenic expression of CAMKⅣ in skeletal muscle increases the amount of GLUT-4 mRNA compared with that in wildtype mice 28) . These findings provide evidence that CaMK, as well as AMPK signaling, mediates the exerciseinduced GLUT-4 biogenesis in skeletal muscle.…”
Section: Mechanisms Underlying Exercise-induced Glut-4 Biogenesismentioning
confidence: 96%